Advances in understanding the pathogenesis of post-traumatic epilepsy: a literature review - Fang, Mingzhu; Liu, Wanyu; Tuo, Jinmei; Liu, Mei; Li, Fangjing; Zhang, Lijia; Yu, Changyin; Xu, Zucai (Frontiers in Neurology, 2023)
Severe head trauma can lead to seizures. Persistent epileptic seizures and their progression are associated with the severity of trauma. Although case reports have revealed that early use of anti-seizure drugs after trauma can prevent epilepsy, clinical case–control studies have failed to confirm this phenomenon. To date, many brain trauma models have been used to study the correlation between post-traumatic seizures and related changes in neural circuit function. According to these studies, neuronal and glial responses are activated immediately after brain trauma, usually leading to significant cell loss in injured brain regions. Over time, long-term changes in neural circuit tissues, especially in the neocortex and hippocampus, lead to an imbalance between excitatory and inhibitory neurotransmission and an increased risk of spontaneous seizures. These changes include alterations in inhibitory interneurons and the formation of new, over-recurrent excitatory synaptic connections. In this study, we review the progress of research related to post-traumatic epilepsy to better understand the mechanisms underlying the initiation and development of post-traumatic seizures and to provide theoretical references for the clinical treatment of post-traumatic seizures.